son Of Performance And Perception Of Undergraduate Medical Students Towards Different Small Group Teaching Strategies - Maryam Habib; Ghazala Mudassir; Mahwish Majid Bhatti; Rifat Nadeem Ahmad (Journal of Rawalpindi Medical College)
Objective: The objective of this study is to evaluate the perception of students towards the effectiveness of small group teaching methods in pathology and to determine their performance in them.